Agony and Ecstasy at the End of the Rainbow - Peires, Jeff (South African Historical Journal, 2009)
The three books are reviewed together because of their shared concern with public history. The review starts with a consideration of the Stolten volume because it incorporates a variety of diverse perspectives, reflecting the present state of South African historiography. Following a detailed discussion, three major themes emerge: (1) whether or not South African historians are agreed on a single 'master narrative' (2) the relationship between History and Heritage (3) the role of university History Departments. The books by Coombes and Callinicos are both more coherent than that edited by Stolten but their very coherence, in the opinion of the reviewer, is only made possible by the omission of key areas of concern which are identified and discussed.